Project Based Learning in the Subject of Embedded System Programming: Students' Conceptual Understanding and Learning Outcomes - Putri, Putri; Purnawati, Purnawati; Mantasia, Mantasia (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
This research is motivated by the low conceptual understanding and learning outcomes of students in the Embedded Systems Programming subject, which is often considered difficult due to the complexity of the material. The main objective of this study is to determine the effectiveness of the project-based learning model (PjBL) in improving conceptual understanding and learning outcomes among students at Vocational School 10 Makassar. The method used is a quasi-experiment with a Nonequivalent Control Group Design. The study population comprises all students from Vocational School 10 Makassar, with samples deliberately chosen: class XI Teli 1 serving as the experimental group and class XI Teli 3 as the control group. Data were collected through test instruments (pre-test and post-test) and student activity observation sheets. The findings showed a significant increase in the experimental class compared to the control class. The experimental class's average score on the post-test went from 41.36% to 83.10%, while the control class's score went from 42.66% to 45.62%. The t-test results showed a significance value <0.05, proving that the PjBL model effectively improved student learning outcomes. This research contribution provides recommendations for educators to implement the PjBL model sustainably as an innovative solution in teaching complex technical materials and its development in other subjects to improve the quality of vocational education.